2007
DOI: 10.1080/01421590701542119
|View full text |Cite
|
Sign up to set email alerts
|

Do medical students watch video clips in eLearning and do these facilitate learning?

Abstract: Students who watched video clips were more active in using collaborative eLearning tools and achieved higher course grades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
87
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(97 citation statements)
references
References 13 publications
6
87
1
3
Order By: Relevance
“…One speculative explanation for these discrepancies is the maturity of students involved in the studies because Martin et al (2004) reported that women use computers more frequently in the work force. More recently, it was also reported that female medical students tended to view video clips for e-learning more frequently than males (Romanov and Nevgi, 2007). It is noteworthy that the gender differences we found were associated only with specific CAI (''Forum'' and ''Flash,'' but not the ''Quiz'' CAI or the portal logins), further suggesting that factors such as CAI design and applicability affect their use by specific students.…”
Section: Discussionmentioning
confidence: 44%
“…One speculative explanation for these discrepancies is the maturity of students involved in the studies because Martin et al (2004) reported that women use computers more frequently in the work force. More recently, it was also reported that female medical students tended to view video clips for e-learning more frequently than males (Romanov and Nevgi, 2007). It is noteworthy that the gender differences we found were associated only with specific CAI (''Forum'' and ''Flash,'' but not the ''Quiz'' CAI or the portal logins), further suggesting that factors such as CAI design and applicability affect their use by specific students.…”
Section: Discussionmentioning
confidence: 44%
“…Video-watching was associated with better course grades in the study by Romanov [10]. Evans [11] also found that there was data to indicate that screencasts had a positive effect on student outcomes.…”
Section: Discussionmentioning
confidence: 79%
“…Sixty-nine college students reported that they felt that the streaming video clips acted as learning reinforcement and that the clips supported their attention and learning styles. Kukulska-Hulme, Foster-Jones, Jelfs, Mallett, and Holland [10] investigated the usefulness of digital video applications in distance learning.…”
Section: Research Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Our literature review found that various studies on digital learning instruction had been conducted in the area of conventional medical education. [17][18][19] These studies have researched topics including active and reflective question usage in web-based instruction; 17 video clip uses and collaborative learning tools in e-learning settings; 20 and the use of an interactive computer-based training program (ICBT) on dementia in different European countries. 21 …”
mentioning
confidence: 99%